TEACHING ENGLISH TO PRESCHOOL CHILDREN THROUGH PLAYING A METHODOLOGICAL APPROACH - Abdivaitova Munira Olim qizi; Qurbonova Gulnoza Abduholiq qizi (Western European Studies, 2025)
This article explores the methodological approach of teaching English to preschool-aged children through play. It highlights the significant role early language acquisition plays in a child's cognitive and social development. The article emphasizes how play-based learning provides an engaging and stress-free environment, where young children can absorb English naturally. Through activities such as games, songs, role-playing, and storytelling, children practice and internalize new language skills while having fun. The article also discusses the benefits of contextual learning, the importance of repetition, and the use of visual aids to support language acquisition
Keywords: preschool children; English language; play-based learning